Milly, Molly and Salt and Pepper - Pittar, Gill (MM House Gisborne, 2003)
The Milly Molly books are written for children between the ages of four and eight. The stories relate the adventures of two girls from different ethnic backgrounds and promote the acceptance of diversity and learning of life skills.